2018
DOI: 10.7554/elife.34039
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous dormancy protects Trypanosoma cruzi during extended drug exposure

Abstract: The ability of the Chagas disease agent Trypanosoma cruzi to resist extended in vivo exposure to highly effective trypanocidal compounds prompted us to explore the potential for dormancy and its contribution to failed drug treatments in this infection. We document the development of non-proliferating intracellular amastigotes in vivo and in vitro in the absence of drug treatment. Non-proliferative amastigotes ultimately converted to trypomastigotes and established infections in new host cells. Most significant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
182
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(212 citation statements)
references
References 30 publications
6
182
1
4
Order By: Relevance
“…While some of the amastigote parasites continue to multiply, a few of them stop their proliferation, even without drug treatment. These none-proliferating amastigotes retain their capacity to differentiate into trypomastigotes as well as their capacity to resume multiplication [34]. Interestingly, in our study, we highlight that at the trypomastigote stage, most of the strains belonging to TcI, are less susceptible (the non wild-type) to both NFX and BZN.…”
Section: Discussionmentioning
confidence: 50%
“…While some of the amastigote parasites continue to multiply, a few of them stop their proliferation, even without drug treatment. These none-proliferating amastigotes retain their capacity to differentiate into trypomastigotes as well as their capacity to resume multiplication [34]. Interestingly, in our study, we highlight that at the trypomastigote stage, most of the strains belonging to TcI, are less susceptible (the non wild-type) to both NFX and BZN.…”
Section: Discussionmentioning
confidence: 50%
“…This may also explain the differing response rate to anti-parasitic treatment among children in comparison with adults, as children have a T-cell profile associated with a more robust clinical response [138]. Additionally, animal model research demonstrates that a small proportion of trypomastigotes are dormant at any given time during infection, and are likely to be protected from anti-parasitic compounds in this state [139].…”
Section: Why Are There Poor Cure Rates In Chronic Patients?mentioning
confidence: 99%
“…An alternative explanation for parasite persistence in the presence of azoles is a complete cessation of amastigote division. While the nature of dormancy in T. cruzi remains under investigation (Sánchez-Valdéz et al, 2018), we report here a protective mechanism that allows for amastigote proliferation in the presence of drug at the population level. Since, slowed growth appears to induce tolerance to azoles but is insufficient to provide resistance; we investigated potential mechanisms to explain the protection from azoles mediated specifically by glutamine restriction.…”
Section: Discussionmentioning
confidence: 78%
“…While spontaneous emergence of latent forms of T. cruzi offers one possible explanation for the failure to achieve parasitological cure following drug treatment (Sánchez-Valdéz et al, 2018), the role of cellular metabolic heterogeneity in recalcitrant T. cruzi infection has not been explored. In previous work, we showed that proliferation of T. cruzi intracellular amastigotes is responsive to modifications in the exogenous growth medium and that media compositions have significant and specific interactions with small molecule inhibitors of parasite metabolism, such as the cytochrome b inhibitor GNF7686 (Dumoulin and Burleigh, 2018).…”
Section: Resultsmentioning
confidence: 99%